Comprehensive spectroscopic and photometric study of pulsating eclipsing binary star AI Hya. Issue 2 (20th January 2023) - Kahraman Aliçavuş, F; Pawar, T; Hełminiak, K G; Handler, G; Moharana, A; Aliçavuş, F; De Cat, P; Leone, F; Catanzaro, G; Giarrusso, M; Ukita, N; Kambe, E
ABSTRACT: The pulsating eclipsing binaries are remarkable systems that provide an opportunity to probe the stellar interior and to determine the fundamental stellar parameters precisely. Especially the detached eclipsing binary systems with (a) pulsating component(s) are significant objects to understand the nature of the oscillations since the binary effects in these systems are negligible. Recent studies based on space data have shown that the pulsation mechanisms of some oscillating stars are not completely understood. Hence, comprehensive studies of a number of pulsating stars within detached eclipsing binaries are important. In this study, we present a detailed analysis of the pulsating detached eclipsing binary system AI Hya which was studied by two independent groups with different methods. We carried out a spectroscopic survey to estimate the orbital parameters via radial velocity measurements and the atmospheric parameters of each binary component using the composite and/or disentangled spectra. We found that the more luminous component of the system is a massive, cool and chemically normal star while the hotter binary component is a slightly metal-rich object. The fundamental parameters of AI Hya were determined by the analysis of binary variations and subsequently used in the evolutionary modelling. Consequently, we obtained the age of the system as 850 ± 20 Myr and found that both binary components are situated in the δ Scuti instability strip. The frequency analysis revealed pulsation frequencies between 5.5 and 13.0 d −1 and we tried to estimate which binary component is the pulsating one. However, it turned out that those frequencies could originate from both binary components.